Evaluation of the scheme on "give way" to buses emerging from bus bays - Tay, Ronald Yong Hwee. (2010)
The objectives of this project is to check the effectiveness of the Give Way To Buses (GWTB) scheme located at bus bays across Singapore, and to identify the problems that arises with the implementation of the scheme. In addition, the perceived effectiveness of the scheme from all parties involved with it will also be investigated. If the scheme is perceived to be ineffective to some extent, mitigating and improvement measures will be proposed.